2015
DOI: 10.1021/acs.bioconjchem.5b00137
|View full text |Cite
|
Sign up to set email alerts
|

D-SP5 Peptide-Modified Highly Branched Polyethylenimine for Gene Therapy of Gastric Adenocarcinoma

Abstract: Peptide-mediated targeting of tumors has become an effective strategy for cancer therapy. Retro-inverso peptides resist protease degradation and maintain their bioactivity. We used the retro-inverso peptide D(PRPSPKMGVSVS) (D-SP5) as a targeting ligand to develop gene therapy for gastric adenocarcinoma. D-SP5 has a higher affinity for human gastric adenocarcinoma (SGC7901) cells compared with that of its parental peptide, L(SVSVGMKPSPRP) (L-SP5). Polyethylenimine (PEI)/pDNA, polyethylene glycol (mPEG)-PEI/pDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Accordingly, the antibody or peptide selected is the key to successful treatment of ovarian tumors (Schiffelers, 2004 ). Currently, the choice of target sites in ovarian cancer focuses on tumor cell surface molecules such as anti-angiogenesis receptor (Koneru et al., 2015 ) (vascular endothelial growth factor [VEGF], epidermal growth factor receptor [EGFR/ErbB]), blood markers of ovarian cancer (Li et al., 2015 ) (mucin 16 [MUC16], human epididymis protein 4 [HE4]), and glycosylated proteases related to suppressing ovarian tumor cell invasion and metastasis (BCL2 interacting killer [BIK]) (Kanhaiya et al., 2017 ). However, most of them do not move forward to clinical trials because of unsatisfactory treatment effects due to the lack of specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the antibody or peptide selected is the key to successful treatment of ovarian tumors (Schiffelers, 2004 ). Currently, the choice of target sites in ovarian cancer focuses on tumor cell surface molecules such as anti-angiogenesis receptor (Koneru et al., 2015 ) (vascular endothelial growth factor [VEGF], epidermal growth factor receptor [EGFR/ErbB]), blood markers of ovarian cancer (Li et al., 2015 ) (mucin 16 [MUC16], human epididymis protein 4 [HE4]), and glycosylated proteases related to suppressing ovarian tumor cell invasion and metastasis (BCL2 interacting killer [BIK]) (Kanhaiya et al., 2017 ). However, most of them do not move forward to clinical trials because of unsatisfactory treatment effects due to the lack of specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Li et al . prepared RI‐SP5‐modified PEG‐PEI as a gene carrier, and both the in vitro and in vivo pharmacodynamics confirmed that RI‐SP5 had a greater therapeutic effect in gastric adenocarcinoma 100…”
Section: Applicationsmentioning
confidence: 75%
“…Retroinverso peptides consisting of D-amino acid residues in reversed sequence adopt side chain topologies similar to the parent peptide but with inverted amide bonds. These modifications have served to improve peptide metabolic stability but with limited capabilities of adopting bio-active peptide α-helical structures necessary for protein binding interactions and downstream biological signaling such as silencing gene expression in certain cancer types (Li et al, 2010(Li et al, , 2015. Main chain replacement with peptide amide bond isosteres (Williams et al, 1994;Hart and Etzkorn, 1999;Chen et al, 2017) have also resulted in important contributions in varying peptide conformation and stereoelectronic effects which impacts peptide bioactivity against receptor targets in cancer (Crombez et al, 2009).…”
Section: Polyamide Backbone Modifications In Peptides and Peptidomimementioning
confidence: 99%
“…Representative examples of polyamide backbone modified cell-targeting peptides described in this study. (A) c(RGDfV) (Kessler, 1997) (Dechantsreiter et al, 1999;Marinelli et al, 2003), (C) Pep42-(Val-Cit) 2 -PABO-Dox (Yoneda et al, 2008), (D) D-SP5 (Li et al, 2015).…”
Section: Figure 3 |mentioning
confidence: 99%
See 1 more Smart Citation